2011
DOI: 10.5194/acp-11-8759-2011
|View full text |Cite
|
Sign up to set email alerts
|

Bounce behavior of freshly nucleated biogenic secondary organic aerosol particles

Abstract: Abstract. The assessment of the climatic impacts and adverse health effects of atmospheric aerosol particles requires detailed information on particle properties. However, very limited information is available on the morphology and phase state of secondary organic aerosol (SOA) particles. The physical state of particles greatly affects particulatephase chemical reactions, and thus the growth rates of newly formed atmospheric aerosol. Thus verifying the physical phase state of SOA particles gives new and import… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 30 publications
(38 reference statements)
4
76
0
Order By: Relevance
“…These SOA particles can undergo phase transitions as a result of changes in relative humidity, and/or O / C level. Addition of hygroscopic sulphuric acid to the SOA liquefied the mixed particles at low RH I , which is consistent with aerosol bounce observations from Virtanen et al (2011) and T g measurements from Koop et al (2011). The phase of the SOA affects corresponding timescales for mass transfer and heterogeneous reactions within the particles (Cappa and Wilson, 2011;Vaden et al, 2011;Shiraiwa et al, 2011), and may influence their ability to serve as cloud condensation nuclei or ice nuclei in the atmosphere.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These SOA particles can undergo phase transitions as a result of changes in relative humidity, and/or O / C level. Addition of hygroscopic sulphuric acid to the SOA liquefied the mixed particles at low RH I , which is consistent with aerosol bounce observations from Virtanen et al (2011) and T g measurements from Koop et al (2011). The phase of the SOA affects corresponding timescales for mass transfer and heterogeneous reactions within the particles (Cappa and Wilson, 2011;Vaden et al, 2011;Shiraiwa et al, 2011), and may influence their ability to serve as cloud condensation nuclei or ice nuclei in the atmosphere.…”
Section: Discussionsupporting
confidence: 67%
“…The discussion above indicates that this might be true independently of whether the sulphate and organic fraction are phase-separated or not. As the particles grow via condensation of oxygenated organic species, the mass fraction and, hence, the effective T g might increase and the particles may solidify (Virtanen et al, 2010(Virtanen et al, , 2011.…”
Section: Phase State and Humidity-induced Phase Transitions Of Mixed mentioning
confidence: 99%
“…Virtanen et al (2011) reported that α-pinene-O 3 SOA bounces off impactor plates as if particles were glassy. Other studies reported that the evaporation kinetics of α-pinene-O 3 SOA was lower than expected by models for liquid droplets, indicating a non-liquid-like state Vaden et al, 2011).…”
Section: Effect Of Rh and Aging On The Viscosity Of Soamentioning
confidence: 99%
“…The phase states of SOA particles have been investigated in more detail by a wide variety of measurement techniques recently. The first indications of an amorphous (semi-)solid state for biogenic SOA particles were deduced by Virtanen et al (2010) and were established in subsequent studies (Virtanen et al, 2011;Cappa and Wilson, 2011;Vaden et al, 2011;Saukko et al, 2012;. These studies have provided a first qualitative estimate of the particle-phase state; however, quantitative values such as the particle-phase bulk diffusion coefficients are essential for model description.…”
Section: Introductionmentioning
confidence: 99%